Analyzing the effect of tax pressure on redistributing income in selected countries - Saeed, Adla A. (Academic Journal of Nawroz University, 2020)
The relationship between tax pressure and income distribution is one of the topics that has taken a large part of the discussion, given that the tax fair rule assumes that the tax is in addition to the redistribution of income, and there is a clear difference in this matter between developed and developing countries and this difference emerges in the form of different directions of the causal relationship Between these two variables and the current research is an attempt to give a picture of the relationship between tax pressure and the distribution of income expressed by a genetic factor in two countries, one of which is a developed country (Germany) and the second of the developing developing countries (Argentina) and a study period that spanned the period 1990-2016 has been used. I used a standard modern methods to reach the nature of the relationship and the research found to the important conclusion that the relationship between the two variables in Argentina were significant while not be a moral relationship in Germany and justifies it of altered types and techniques of tax, as well as the variation in the level of economic cooperation between the two countries development.